PERBANDINGAN KADAR HAEMOGLOBIN DAN HEMATOCRIT PADA REMAJA PUTRI SEBELUM DAN SESUDAH MENSTRUASI DI SMA MUHAMMADIYAH 5 PALEMBANG - Enderia Sari (Jurnal Inspirasi Kesehatan, 2023)
Background:. Young women have ten times greater risk of suffering from anemia compared to young men. This is because young women experience menstruation every month and are in a period of growth, so they need more iron intake Objective: Postpartum mothers can understand and practice proper breastfeeding techniques and umbilical cord care. Methods: The research design used was a pre-experimental design (one group pretest posttest). The population in this study was a total population of 91 respondents, and there were 8 respondents who dropped out. The data was carried out using the Wilcoxon Test, with a 95% confidence level. Results: From the premenstrual analysis, the mean hemoglobin concentration was 13.1 g%. The maximum hemoglobin level was 14.8 g% and the minimum value was 10.6 g%. In post menstruation, the results of the mean hemoglobin examination were 13.1 g%, the maximum hemoglobin level was 15.0 g% and the minimum value was 10.3 gr. In Bivariate analysis From the results of the Wilcoxon test, the significance number shows the pre and post hemoglobin level of 0.74 and the hematocrit level of 0.435. Because the p value > 0.05, it can be concluded that there is no significant difference before and after examination of hemoglobin and hematocrit levels. Conclusion: from the analysis of pre- and post-menstrual hemoglobin and hematocrit examinations, there is no significant difference to pre- and post-menstrual examinations of pre- and post-menstrual hemoglobin and hematocrit levels.